Role of High-Frequency Oscillation in Locating an Epileptogenic Zone for Radiofrequency Thermocoagulation - Xu, Xin; Yu, Xingguang; Kang, Guixia; Mao, Zhiqi; Cui, Zhiqiang; Pan, Longsheng; Zong, Rui; Tang, Yuan; Wan, Ming; Ling, Zhipei (Frontiers in Human Neuroscience, 2021)
Radiofrequency thermos-coagulation has been proposed as a first-line surgical treatment option for patients with drug-resistant focal epilepsy associated with gray matter nodular heterotopia. Excellent results on seizures have been reported following coagulation of single, unilateral radiofrequency thermos-coagulation that has been performed in the ictal high-frequency discharge, mainly in the fast rhythm and low voltage initiation area. Complex cases (gray matter nodular heterotopia plus other malformations of cortical development) don’t have good outcome with radiofrequency thermos-coagulation. Yet, there are few researches studying the effect of high frequency Oscillation to locate epileptogenic zone for thermos-coagulation on unilateral in the drug-resistant epilepsy with bilateral gray matter nodular heterotopia. Here, we present a case of drug-resistant focal epilepsy with bilateral gray matter nodular heterotopia treated using radiofrequency thermos-coagulation on unilateral gray matter nodular heterotopia and overlying cortex guided by stereotactic electroencephalogram and followed up for 69 months. Twenty-four-hour electroencephalogram recordings, seizure frequency, post-radiofrequency thermos-coagulation magnetic resonance imaging, and neuropsychological tests were performed once yearly. To date, this patient is seizure-free, the electroencephalogram is normal, neuropsychological problems have not been found, and the trace of radiofrequency thermos-coagulation was clearly shown on magnetic resonance imaging. So far, his only take a little bit antiepileptic-drugs. Overall, radiofrequency thermos-coagulation on unilateral in the drug-resistant focal epilepsy with bilateral gray matter nodular heterotopia can achieve long-term effects, lasting up to and perhaps longer than 69 months. Ictal high-frequency oscillation（fast ripple）inside heterotopia and the overlying cortex may be the keys to the 69-month effect of radiofrequency thermos-coagulation on unilateral in the drug-resistant focal epilepsy with bilateral gray matter nodular heterotopia.